Identified improvements of wireless sensor networks in smart grid: issues, requirements and challenges. (2016) - Hosni, Ines; Hamdi, Noureddine
Communications infrastructure is a basic part for the success of smart grid. Optimisation of energy consumption in the future intelligent energy networks (smart grids) will be based on the integrated near real-time between the different elements of grid network communications. Through a communication infrastructure, a smart grid can improve the reliability of power, eliminate power outages, and optimise energy consumption. The network gets smarter by improving detection, so the most important element that makes the smart grid is wireless sensor networks. Among them, one of the most important applications is a sensor data collection. This paper discusses some of communications research challenges and opportunities in the areas of smart grid and smart meters. In particular, we focus on some of the main communications challenges to achieve interoperability and future proof, smart grid/metering networks. We describe the basic taxonomy and propose to break the network data collection of wireless sensors.